Brittle fracture studied by ultra‐high‐speed synchrotron X‐ray diffraction imaging. Issue 4 (30th July 2022) - Petit, Antoine; Pokam, Sylvia; Mazen, Frederic; Tardif, Samuel; Landru, Didier; Kononchuk, Oleg; Ben Mohamed, Nadia; Olbinado, Margie P.; Rack, Alexander; Rieutord, Francois
Abstract : Crack propagation in a silicon single‐crystal wafer is tracked in situ using synchrotron‐based ultra‐high speed X‐ray diffraction imaging. The high spatio‐temporal resolution reached in diffraction imaging mode allows for assessing different parameters such as crack velocity or post crack movements of the separated wafers. Abstract : In situ investigations of cracks propagating at up to 2.5 km s −1 along an (001) plane of a silicon single crystal are reported, using X‐ray diffraction megahertz imaging with intense and time‐structured synchrotron radiation. The studied system is based on the Smart Cut process, where a buried layer in a material (typically Si) is weakened by microcracks and then used to drive a macroscopic crack (10 −1  m) in a plane parallel to the surface with minimal deviation (10 −9  m). A direct confirmation that the shape of the crack front is not affected by the distribution of the microcracks is provided. Instantaneous crack velocities over the centimetre‐wide field of view were measured and showed an effect of local heating by the X‐ray beam. The post‐crack movements of the separated wafer parts could also be observed and explained using pneumatics and elasticity. A comprehensive view of controlled fracture propagation in a crystalline material is provided, paving the way for the in situ measurement of ultra‐fast strain field propagation.